Analisis Kepuasan Masyarakat terhadap Layanan KUA Menggunakan Algoritma K-Means dan C4.5 - Nabilah Putri Permana; Agung Ramadhanu; Gunadi Widi Nurcahyo (Journal of Information System Research (JOSH), 2026)
The Office of Religious Affairs (KUA) is an institution under the Ministry of Religious Affairs that provides religious services to the community, including marriage administration. Improving the quality of public services requires data-driven evaluation to measure the level of public satisfaction with the services provided. This study aims to analyze the level of community satisfaction with the services of the Office of Religious Affairs in Tebing Tinggi District using a combination of the K-Means Clustering and C4.5 algorithms. The research data were obtained from questionnaires distributed to community members who used KUA services. The K-Means algorithm was applied to group community satisfaction data based on the similarity of attribute values, while the C4.5 algorithm was used to build a classification model that generates decision rules to predict the level of community satisfaction. The results show that the proposed methods are able to group satisfaction levels in a structured manner and produce a classification model with high accuracy in analyzing public service satisfaction. The findings of this study are expected to support KUA in evaluating and improving service quality, as well as provide a reference for the application of data mining techniques in analyzing community satisfaction in public service sectors.